Understanding reader navigation patterns in multi-path hypertext fiction: A case study approach to Patchwork Girl - Nurul Hijja Mazlan; Candra Rahma Wijaya Putra; Hary Sulistyo (Lingua Technica: Journal of Digital Literary Studies, 2025)
The rise of hypertext fiction has transformed narrative structures, challenging traditional reading behaviors and comprehension strategies. This study aims to investigate how readers navigate and engage with Patchwork Girl, a seminal work in hypertext fiction, focusing on navigation patterns, motivations, and their impact on comprehension and engagement. Employing a qualitative case study approach, the research involved 110 undergraduate English majors, using observations, interviews, and thematic analysis to uncover patterns and insights. Findings revealed three dominant navigation strategies—linear, exploratory, and random—each influenced by motivations such as curiosity, thematic alignment, and a desire for agency. Linear navigation resulted in higher comprehension, while exploratory navigation fostered moderate engagement, and random navigation led to cognitive overload and fragmented understanding. These findings underscore the importance of balancing narrative complexity with user guidance in hypertext design, offering valuable implications for digital storytelling and educational applications.